1992
DOI: 10.1016/0002-9149(92)90146-p
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic risk factors of luminal narrowing after coronary balloon angioplasty using balloon measurements to reflect stretch and elastic recoil at the dilatation site

Abstract: on behalf of the CARPORT Study Group Because many ongoing clinical restenosis prevention trials are using quantitative angiography to assess whether a drug is capable of reducing the amount of intimal hyperplasia, quantitative angiographic risk factors for angiographic luminal narrowing after balloon angioplasty were determined, including stretch and elastic recoil at the dilatation site. Quantitative analysis was performed on 666 lesions in 575 patients during angioplasty and at 6-month follow-up. Stretch was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 25 publications
1
10
1
1
Order By: Relevance
“…In previous studies, a larger relative gain was observed to be an independent predictor of restenosis, with a direct relationship between relative gain and the subsequent relative loss at follow-up 11 16…”
Section: Discussionmentioning
confidence: 83%
“…In previous studies, a larger relative gain was observed to be an independent predictor of restenosis, with a direct relationship between relative gain and the subsequent relative loss at follow-up 11 16…”
Section: Discussionmentioning
confidence: 83%
“…4,5 These interventional procedures result in endothelial denudation with intimal and medial damage, which induces substantial local inflammation. This inflammation is manifested by monocyte infiltration as well as inflammatory mediator and growth factor production.…”
mentioning
confidence: 99%
“…In a study of pooled data by Foley et al [11], increased coronary size was an independent predictor of a larger MLD and of reduced late luminal loss, thereby a lower restenosis rate. It has also been established that the overall net gain remains greater in vessels dilated with greater acute luminal gain, despite a greater absolute loss in follow‐up [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have determined angiographic or intravascular ultrasound (IVUS) predictors of in‐stent restenosis using the “bigger is better” hypothesis [12–15]. It has been well recognized that achieving greater acute luminal gain after coronary stenting allows greater net gain despite greater absolute loss [16]. During the study period, coronary stent for vessel diameter greater than 4 mm is not available except the hand‐crimped unmounted Palmaz biliary (PB) stents.…”
Section: Introductionmentioning
confidence: 99%